Bone Regeneration: A Multi‐Functional Implant Induces Bone Formation in a Diabetic Model (Adv. Healthcare Mater. 18/2020). Issue 18 (23rd September 2020) - Khorsand, Behnoush; Acri, Timothy M.; Do, Anh‐Vu; Femino, John E.; Petersen, Emily; Fredericks, Douglas C.; Salem, Aliasger K.
Abstract : In article number 2000770 by Aliasger K. Salem and co‐workers, the local delivery of insulin, Vitamin D3 metabolites, and BMP‐2 and FGF‐2 genes from a collagen scaffold is investigated to promote bone formation in Type‐2 diabetic rats. The ectopic formation of bone in diabetic rats suggests this approach has strong potential for bone regeneration in diabetic patients.